Ilustrasi Praktik Diskriminasi Pengampuan Penyandang Disabilitas Mental dan Tinjauan Maslahat dalam Hukum Islam - M. Syafi’ie (Jurnal Hukum IUS QUIA IUSTUM, 2024)
The discourse on the legal capacity of persons with mental disabilities is currently increasing among the observers of the rights of the disabled, including Islamic law observers. The present situation is driven by the demands of the disabled community who prefers the policy on giving parole to be abolished, and hopes for it to be altered with another newer policy known as ‘supported decision making’. Parole is considered to be discriminatory, as it violates human rights, and eradicates the rights of certain legal subject which such rights are categorized as the non-derogable rights. This article touches upon two issues, first, it illustrates the practice of offering parole in a way that is considered discriminatory for persons with mental disabilities. Second, it reviews the concept of benefit in Islamic law by looking at the practice of forgiveness that has been conducted. The method used in this research is empirical juridical. The research concluded that, firstly, the parole policy has had an impact on discriminatory practices, violating the rights of persons with mental disabilities, and should be abolished and replaced with a newer policy model, namely ‘supported decision making’, which means that persons with mental disabilities are not replaced (substituted) but facilitated by the creation of a system that provides support in the decision making, especially legal decisions. Second, in Islamic legal thoughts, the policy of giving forgiveness is considered not in line with the concept of benefit. Benefit means that the most essential feature in the legal system is the benefit, public interest, and positive outcomes resulting from the said system. An important conclusion in this research confirms that the parole policy has had a negative impact on persons with mental disabilities, thus should be replaced with a policy of ‘supported decision making’ which is considered useful, non-discriminatory, and in line with the rights of persons with disabilities.Keywords: Benefits; Parole; Persons with Mental Disabilities; Supported Decision Making. AbstrakDiskursus kecakapan hukum bagi penyandang disabilitas mental saat ini menguat di kalangan pengkaji disabilitas, termasuk di kalangan pengkaji hukum Islam. Situasi tersebut didorong oleh tuntutan komunitas penyandang disabilitas yang menghendaki penghapusan kebijakan ‘pengampuan’, dan harapannya diganti dengan kebijakan baru yang dikenal dengan ‘supported decision making’. Pengampuan dinilai diskriminatif, melanggar hak asasi manusia, dan menghilangkan hak atas sebagai subyek hukum yang merupakan hak terkategori non derogable rights. Tulisan ini meneliti dua hal, pertama, ilustrasi praktik pengampuan sehingga dianggap diskriminatif bagi penyandang disabilitas mental. Kedua, tinjauan konsep maslahat dalam hukum Islam dalam melihat praktik pengampuan yang terjadi. Metode penelitian yang digunakan ialah yuridis empiris dengan pendekatan sosiologis. Penelitian menghasilkan kesimpulan, pertama, kebijakan pengampuan telah berdampak terhadap praktik diskriminatif, melanggar hak penyandang disabilitas mental, dan sudah selayaknya dihapuskan dan digantikan dengan model kebijakan baru yaitu ‘supported decision making’ yang artinya bahwa penyandang disabilitas mental tidak digantikan (substitusi) tetapi difasilitasi dengan diciptakannya sistem pemberian dukungan dalam pengambilan keputusan, utamanya keputusan yang berdimensi hukum. Kedua, dalam pemikiran hukum Islam, kebijakan pengampuan dinilai tidak sejalan dengan konsep maslahat. Maslahat bermakna bahwa yang terpenting dalam sistem hukum ialah faedah, kepentingan umum, dan manfaat positif yang dihasilkan dari sebuah sistem. Kesimpulan penting dalam penelitian ini menegaskan bahwa kebijakan pengampuan telah berdampak negatif bagi penyandang disabilitas mental, dan sudah selayaknya digantikan dengan kebijakan ‘'supported decision making’ yang dinilai berguna, tidak diskriminatif, dan sejalan dengan hak-hak penyandang disabilitas.Kata Kunci: Maslahat; Pengampuan; Penyandang Disabilitas Mental; Supported Decision Making.